DIALEKTIKA ISLAM DAN BUDAYA LOKAL: Basis Sosio-Kultural Pembentukan Islam Nusantara - Fajar Pratama, Zacky; Syakila Nurdini; Muhammad Suyadi Badar; Muhamad Parhan (Jurnal Studi Islam dan Sosial, 2025)
This study examines the dialectic between Islam and local culture in Indonesia through Vygotsky’s socio-cultural theory to explain how the interaction between religion and tradition produces a contextual form of religiosity. Using a qualitative approach with content analysis, this research explores ethnographic texts, Islamic documents, and local cultural practices such as kenduri, Haji Bawakareng, baayun maulid, barapen, and the Minangkabau philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah. The data were interpreted to identify forms of social, symbolic, and cultural mediation in the internalization of Islamic values. The findings show that Islam Nusantara represents an active dialectical process that creates a communal zone of proximal development where religion and culture interact productively in shaping social consciousness. Theoretically, the study extends Vygotsky’s framework by demonstrating that symbolic mediation functions not only in individual cognition but also in collective religious construction. The results affirm Islam Nusantara as a reflective and moderate model of Islam that adapts to modernity, engages with cultural plurality, and strengthens social cohesion within Indonesian society.